2013
DOI: 10.4236/arsci.2013.12002
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic diagnosis and the biopsy technique: Important considerations

Abstract: Preimplantation genetic diagnosis allows to test the genetic status of embryos prior to implantation. In order to obtain genetic material, on which carry out a genetic diagnosis, a procedure named embryo biopsy is required. In the last two decades, embryo biopsy at the cleavage stage has been the mostly performed procedure. However, recently, alternative methods allowing the retrieval of a larger number of cells (blastocyst stage biopsy), or representing a valid alternative to overcome ethical issues (polar bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The number of cells to be biopsied in the cleavage stage embryo may be one of the main issues in PGD [Greco et al 2013]. Some studies reported that biopsy of more than one blastomere from a cleavage stage embryo can negatively affect further development, blastocyst formation, and subsequently clinical outcomes [De Vos et al 2009;Goossens et al 2008].…”
Section: Discussionmentioning
confidence: 99%
“…The number of cells to be biopsied in the cleavage stage embryo may be one of the main issues in PGD [Greco et al 2013]. Some studies reported that biopsy of more than one blastomere from a cleavage stage embryo can negatively affect further development, blastocyst formation, and subsequently clinical outcomes [De Vos et al 2009;Goossens et al 2008].…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been adapted for comprehensive molecular cytogenetic analysis of metaphase II oocytes and their polar bodies [ 25 ], cleavage stage embryos [ 17 , 26 ], and blastocysts [ 27 ]. In this latter case, biopsy of trophectoderm (TE) cells can have several advantages with respect to biopsy of blastomeres at day 3 of embryo development [ 28 ]. Because a larger number of cells can be biopsied from a blastocyst, it is expected that more accurate information can be obtained as compared to one-cell or a few-cell biopsy from cleavage stage embryos, thus reducing the risk of misdiagnosis of embryonic chromosomal mosaicism.…”
Section: Introductionmentioning
confidence: 99%
“…Potential sources of genetic material are: first (1 PB) and second polar bodies (2 PB), day 3 embryo blastomeres, and blastocyst trophectoderm cells (Brezina et al 2013 ; Greco et al 2013 ). All these techniques require several laboratory manipulation procedures before embryo transfer: oocyte zona pellucida laser drilling, embryo biopsy, cryopreservation and thawing, that might affect embryo survival and its implantation potential (Scott et al 2013a ; Zhang et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%